(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines parents’ perceptions of the Mid-Day Meal (MDM) Programme in Telangana State, India, focusing on its impact on school enrollment, attendance, and nutrition. A qualitative research approach was employed, involving in-depth interviews with 20 parents using a structured questionnaire to gather detailed insights into their experiences and opinions. Thematic analysis was used to identify key themes from the qualitative data. The findings indicate that parents view the MDM Program as a crucial incentive for enhancing school attendance and a significant contributor to improving child nutrition. The study underscores the need for increased awareness and the resolution of challenges associated with the program, providing valuable insights for policymakers to optimize its implementation and overall impact.